การผลิตน้ำส้มควันไม้จากไม้สะเดาด้วยเตาไพโรไลซิสแบบแก๊สหมุนวนปิด (PRODUCING WOOD VINEGAR FROM NEEM WOOD BY CLOSED CIRCULATION GAS PYROLYSIS KILN) - ภูวดิน ติณกร; ขันติโกมล ปรีชา; พลสงคราม ไมตรี (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2018)
บทความวิจัยนี้มีวัตถุประสงค์เพื่อนำเสนอสภาวะที่เหมาะสมในการผลิตน้ำส้มควันไม้ด้วยเตาไพโรไลซิสแบบแก๊สหมุนวนปิดและองค์ประกอบทางเคมีของน้ำส้มควันไม้ที่ผลิตได้ โดยทำการทดลองกับเตาไพโรไลซิสขนาดความจุ 0.018 m3 ซึ่งประกอบด้วย ชุดทำความร้อนไฟฟ้า ห้องไพโรไลซิส คอนเดนเซอร์ และพัดลมอัดอากาศ ใช้แก๊สที่ผลิตได้ในระบบวนกลับมาใช้เป็นของไหลที่ให้ความร้อนแก่ชีวมวลแบบปิด แก๊สส่วนเกินจะทำการบรรจุในถุงเก็บแก๊ส ใช้ชีวมวล คือ ไม้สะเดา จำนวน 2 กิโลกรัม ความชื้น 13.74% และ 0.87% ทำการศึกษาที่อุณหภูมิแก๊สเข้าเตาไพโรไลซิสที่ 300, 350 และ 400oC ใช้หลักการสลายโครงสร้างของชีวมวลด้วยวิธีการทางเคมีความร้อน ซึ่งไม่ได้มีการเผาไหม้โดยตรง อัตราการป้อนแก๊สร้อนจะทำการปรับเปลี่ยนอัตราการไหลเชิงปริมาตร 3 ค่า คือ 0.0112, 0.0126 และ 0.0137 m3/s จากผลการศึกษาเชิงทดลองพบว่า สภาวะที่เหมาะสมในการผลิตน้ำส้มควันไม้ด้วยเตาไพโรไลซิสแบบแก๊สหมุนวนปิดคือ อัตราการไหลของแก็สหมุนวนที่ 0.0126 m3/s และอุณหภูมิแก๊สเข้าเตาไพโรไลซิสที่ 400oC ให้ผลผลิตน้ำส้มควันไม้ 36.55% โดยน้ำหนัก สำหรับชีวมวลความชื้นสูง นอกจากนี้ยังพบว่า ปริมาณน้ำส้มควันไม้จะเพิ่มขึ้นตามอุณหภูมิในการไพโรไลซิสเนื่องจากอุณหภูมิเตาที่สูงขึ้นจะส่งผลต่ออัตราการสลายตัวโครงสร้างของชีวมวลได้เร็วขึ้น แต่สำหรับอัตราการไหลของแก็สหมุนวนที่สูงกลับให้ปริมาณน้ำส้มควันไม้ลดลงเนื่องจากอัตราการไหลของแก๊สหมุนวนที่สูงนั้นจะพาความร้อนไปอย่างรวดเร็วทำให้เวลาการไพโรไลซิสไม่เพียงพอ ความร้อนจะถูกใช้ประโยชน์ไม่เต็มที่สำหรับการวิเคราะห์องค์ประกอบทางเคมีของน้ำส้มควันไม้ที่ผลิตได้ พบว่า มีกรดอาซีติกเป็นสารประกอบหลักมีค่าเท่ากับ 44.46% ส่วนสารประกอบฟีนอลมีค่าเท่ากับ 0.45% และมีความเป็นกรด-ด่างอยู่ที่ 2.976 คำสำคัญ: น้ำส้มควันไม้ เตาไพโรไลซิส แก๊สหมุนวนปิด ไม้สะเดา The present research article aims to study the optimal conditions for producing wood vinegar by the closed circulation gas pyrolysis kiln and chemical composition of the wood vinegar produced. The capacity of the pyrolysis kiln was 0.018 m3. The closed gas circulation pyrolysis kiln consists of heater, pyrolysis chamber, condenser and blower. The producer gas in the system was employed as working fluid which circulated in the system. The excess gas was filled into the gas bag. Neem wood was examined as biomass. The consumption of biomass was 2 kg. with the moisture content of 13.74% and 0.87%. The gas temperature before entering the pyrolysis kiln was varied at 300, 350 and 400oC. The pyrolysis process was used to the principal structural decomposition of biomass by means of chemical heat, which does not burn directly. Gas circulation flow rate will be adjusted 3 levels at 0.0112, 0.0126 and 0.0137 m3/s. The experimental results indicated that the optimal conditions for producing wood vinegar by the closed circulation gas pyrolysis kiln showed gas circulation flow rate at 0.0126 m3/s and gas temperature before entering the pyrolysis kiln 400oC. The wood vinegar production for high moisture content biomass was 36.55% by weight. Furthermore found that wood vinegar quantity will increased with increasing of the gas temperature in the pyrolysis process, due to higher temperature will affect to the rate of structural decomposition of biomass. But the high flow rate of gas circulation showed decreasing of wood vinegar quantity, due to heat will be removed quickly that make the pyrolysis time was not sufficient. The heat in the system was not fully exploited. The results from the chemical analysis by Gas Chromatograph-Mass Spectrometer (GC-MS) found that acetic acid was a main compound of wood vinegar which was 44.46%, and phenol was 0.45%. The result of testing acidity - pH was 2.976. Keywords: Wood Vinegar, Pyrolysis Kiln, Closed Circulation Gas, Neem Wood